Resource Recovery of the Wastewater-Derived Nutrients into Algal Biomass Followed by Its Cascading Processing to Multiple Products in a Circular Bioeconomy Paradigm - Muhammad Nabeel Haider; Chen-Guang Liu; Tanveer A. Tabish; Deepanraj Balakrishnan; Pau-Loke Show; Shaza Yehya Abdulhamed Qattan; Munazza Gull; Muhammad Aamer Mehmood (Fermentation, 2022)
The cultivation of Plectonema terebrans BERC10 in wastewater and integrating the wastewater-derived biomass followed by its processing for multiple products in a biorefinery could help in achieving environmental sustainability and cost effectiveness. This study evaluated the resource recovery potential of the cyanobacterium Plectonema terebrans BERC10 from urban wastewater followed by the cascading processing of the biomass into multiple bioproducts. The annual biomass productivity ranged from 0.035–0.064 gL−1d−1 and contained 40–46% lipids and 20–38% protein. The cascading processing of the biomass resulted in multiple products, including 53 mgg−1 of high-value pigments and high-quality biodiesel in accordance with American and European standards. The pigment-free and de-fatted residual biomass was used as a sole feedstock (30–70 gL−1) to produce enzymes and mycoproteins via fungal fermentation employing Aspergillus niger and Aspergillus oryzae. Interestingly, A. oryzae produced 28 UmL−1 of α-amylase and the final residues were mycoproteins after 96 h. Furthermore, the strain removed 80–90% of total phosphorous, 90–99% of total nitrogen, and significantly lowered the COD, BOD, and TDS of urban wastewater. The data demonstrated that P. terebrans has substantial potential for resource recovery and could become a candidate for a wastewater-derived algal biorefinery.